2002
DOI: 10.1677/jme.0.0280165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative activity of pulsed or continuous estradiol exposure on gene expression and proliferation of normal and tumoral human breast cells

Abstract: Intranasal administration of hormone replacement therapy presents an original plasma kinetic profile with transient estrogen levels giving rise to the concept of pulsed therapy. To further understand the molecular effects of this new therapy, we have compared the effects of pulsed and continuous estradiol treatments on two critical aspects of estradiol action: gene expression and cell proliferation. Cells were stimulated with estradiol as 1-h pulsed or 24-h continuous treatments at concentrations such that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…Here, we focus on the roles of some genes that are actively involved in tumorigenesis, proliferation and apoptosis. It has been reported that pulsed and continuous E2 administration exerted the same effect on gene expression and cell proliferation in normal and in cancerous breast cells [7], but our results showed that continuous E2 (10 −9 M) treatment did not induce proliferation in HUVECs, and that pulsed treatment elicited, surprisingly, an inhibitory effect on cell proliferation at the same dosage of exposure. This anti-proliferative effect might be important therapeutically.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Here, we focus on the roles of some genes that are actively involved in tumorigenesis, proliferation and apoptosis. It has been reported that pulsed and continuous E2 administration exerted the same effect on gene expression and cell proliferation in normal and in cancerous breast cells [7], but our results showed that continuous E2 (10 −9 M) treatment did not induce proliferation in HUVECs, and that pulsed treatment elicited, surprisingly, an inhibitory effect on cell proliferation at the same dosage of exposure. This anti-proliferative effect might be important therapeutically.…”
Section: Discussioncontrasting
confidence: 76%
“…This suggests a possible differential effect of pulsed E2 administration on vascular biology such that the development of capillary congestion and edema is less in endometrial and breast tissues during pulsed E2 therapy. It also has been demonstrated that pulsed exposure is as efficient as continuous exposures on the expression of endogenous or transfected estrogen-regulated genes and proliferation in normal and malignant human breast cells [7]. As the pulsed administration (nasal spray of estradiol) and continuous administration (oral or patches) lead to different pharmacokinetics profiles and subsequent E2 plasma levels in postmenopausal women, it is important to compare both routes of administration with regard to the modulation of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Control cells were treated with ethanol as vehicle (1:1000). Treatments were carried out in a phenol red-free medium containing 5% dextran-charcoal-stripped serum for a period of 48 h in breast cancer cells and 96 h in HBE cells due to difference in doubling time and optimal conditions as previously reported [16][17][18][19]. Steroid concentrations were chosen according to two criteria.…”
Section: Steroid Treatmentsmentioning
confidence: 99%
“…Estrogen receptor quantification Hippocampal ERs were quantified by [2,4,6, H(N)]-17b-estradiol radioligand binding (1 nM; specific activity, 95 Ci/mmol; displaced by 1 lM diethylstilbestrol [18,70,71]). The entire right hippocampus was assayed to ensure consistency between samples, as the density and subtype of the estrogen receptor varies between dorsal and ventral aspects of the hippocampus [72,73].…”
Section: Marriott Unpublished Observations)mentioning
confidence: 99%
“…The regimen of estrogen replacement also appears to play a role and studies have begun to address whether pulsed administration of estrogens may be more efficacious [6][7][8]. Quality of life in women is improved by pulsed, but not constant estrogen therapy [9].…”
Section: Introductionmentioning
confidence: 99%